INTRINSIC CARRIER CONCENTRATION AND THE FUNDAMENTAL HIGH-TEMPERATURE OPERATING LIMIT OF WIDE-BANDGAP SEMICONDUCTORS - M.Kh.Kuchkarov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. The replacement of silicon by wide-bandgap (WBG) semiconductors such as 4H-SiC and GaN is the central trend in modern power and high-temperature electronics. Their advantage is governed by the equilibrium statistics of charge carriers: a  doped  device  operates  correctly  only  while  the  thermally  generated  intrinsic population  n i   remains  far  below  the  net  doping.  Using  the  classical  nondegenerate carrier statistics, we compute n i (T) and the intrinsic-onset temperature T i  on a common footing for Ge, Si, GaAs, 4H-SiC, and GaN with a temperature-dependent gap. At 300 K, n i  spans about 23 orders of magnitude across the set, and T i  (defined at a 10 16  cm−3  doping level) rises almost linearly with the band gap, reaching about 1550–1590 K for SiC and GaN versus 659 K for Si. The band gap is thus identified as the single dominant lever setting the fundamental high-temperature ceiling of a semiconductor device.